Broadening placement opportunities for nursing students through an indirect supervision model - Jonathan Hay; Kate H. Knight; Mark Arnold; Pamela Donaghy-Binks (BMC, 2024)
Abstract Background Higher Education Institutions struggle to fill national deficits in student placement capacity, especially in social care and the voluntary sector. The Indirect Placement Supervision and Assessment Model and its holistic focus helps redress this deficit. Methods A Microsoft Forms survey was distributed to a self-selecting sample of 50 students, placement providers, and university staff, all of whom had been involved in indirect supervision as either an assessor, student, or supervisor. Results Three key themes emerged from the data collected; responses suggested that the model generated greater placement variety, increased placement capacity, and brought about reciprocal gains in the learner-supervisor matrix. Conclusion The study's key implication for healthcare institutions pertains to a strong evidence base that the indirect supervision model provides an efficient means of broadening nursing placement variety and capacity alike.